Peran Orang Tua Dalam Memotivasi Remaja Untuk Mengikuti Ibadah di GKS Jemaat Lamboya - Mariana Hunga; Yakobus Adi Saingo (Jurnal Penelitian Multidisiplin Ilmu, 2023)
Parents have a quite important and significant role in a family. Especially in Christian families, parents must be able to nurture their teenage children to become individuals who truly believe in the Lord Jesus Christ and practice Biblical values, one of which is manifested by devotion to worship. The aim of this research is to discuss the role of parents in motivating teenagers to attend worship at the GKS Lamboya congregation. The method used is qualitative with a descriptive approach. In this research, we will apply a purposive sampling pattern, namely collecting data by interviewing 10 parents with the criteria of having teenage children aged 14-20 years and attending church at the GKS Lamboya Congregation. Data were analyzed reductively and presented descriptively. The results of the research show that: 1) parents have tried to provide correct spiritual education to make their teenage children aware of being willing to go to church. 2) Parents have tried to provide proper protection for their teenage children so that they do not make the wrong friends and cause them to be lazy about going to church. 3) parents continue to motivate their teenage children to become active individuals in worship. 4) parents position themselves as spiritual servants for their teenage children so that they become individuals who always prioritize spiritual matters, including being active in worship. 5) parents position themselves not stiffly with their children in beautiful interactions.